Postavení společníka v s.r.o. - Jandová, Andrea (2008)
This diploma thesis describes the position of partner (member) in a Czech limited liability company and interprets all legal aspects of his rights and obligations. The essay focuses on descriptions of one of the most favorite legal forms and its main characteristics. The aim of the essay is to outline the opportunities of this legal form and issues relating to sometimes uneasy possibilities of the entrepreneur. It points out the advantage of being not liable for the company´s debts after paying off all the members´ capital contributions and analyses the consequences of interest ownership. Moreover, the capital contribution determines the amount of rights and duties of the members that is the main object of this diploma.